Absolute quantification of imipramine and its metabolites in vivo utilizing calibrators from radiolabeled in vitro incubations. (February 2016) - Bhutani, Priyadeep; Shah, Devang; Varkhede, Ninad; Mandlekar, Sandhya; Chacko, Silvi; Subramanian, Murali
Background: We have demonstrated the use of a single-point calibration approach, derived from in vitro metabolite identification studies utilizing radiolabeled imipramine, that allows for the quantitation of metabolites from in vivo studies in the absence of metabolite synthetic standards.Results: From the in vivo study of imipramine in rats, the concentration of parent and metabolites were determined using the single-point calibration approach. Sixty seven percent of the dosed imipramine was recovered within 24 h, with 95 and 5% of drug-related material detected in feces and urine, respectively.Conclusion: Using a novel single-point calibration approach from radiolabeled in vitro studies, we quantified metabolites in vivo and determined various disposition pathways.